2014
DOI: 10.1371/journal.pone.0111602
|View full text |Cite|
|
Sign up to set email alerts
|

Behavior Change Pathways to Voluntary Medical Male Circumcision: Narrative Interviews with Circumcision Clients in Zambia

Abstract: As an HIV prevention strategy, the scale-up of voluntary medical male circumcision (VMMC) is underway in 14 countries in Africa. For prevention impact, these countries must perform millions of circumcisions in adolescent and adult men before 2015. Although acceptability of VMMC in the region is well documented and service delivery efforts have proven successful, countries remain behind in meeting circumcision targets. A better understanding of men's VMMC-seeking behaviors and experiences is needed to improve c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…The booths were managed by peer promoters and health facility staff and addressed the women's questions on VMMC and were also used to coach women on how to encourage male partners who were undecided or reluctant to seek circumcision. Several studies have shown that women influence their partners’ decision to be circumcised [23,32,33]. Providing correct information to women empowers them to play this role and may be an effective way of reaching married adult men.…”
Section: Discussionmentioning
confidence: 99%
“…The booths were managed by peer promoters and health facility staff and addressed the women's questions on VMMC and were also used to coach women on how to encourage male partners who were undecided or reluctant to seek circumcision. Several studies have shown that women influence their partners’ decision to be circumcised [23,32,33]. Providing correct information to women empowers them to play this role and may be an effective way of reaching married adult men.…”
Section: Discussionmentioning
confidence: 99%
“…Despite adult VMMC scale-up in the 14 priority countries over the last 4–5 years, researchers have not yet managed to adequately dissect the adult VMMC decision-making process. Some research groups have attempted to do this and have identified some of the important factors while acknowledging that their understanding of the process is incomplete [3436]. They have, however, identified a range of motivators, including those unrelated to risk of HIV including improved hygiene, perceptions of responsible masculine choice, perceptions of sexual partner preferences, and improved health for female sexual partners (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…They have, however, identified a range of motivators, including those unrelated to risk of HIV including improved hygiene, perceptions of responsible masculine choice, perceptions of sexual partner preferences, and improved health for female sexual partners (e.g. reduced risk of cervical cancer) [34, 36]. …”
Section: Discussionmentioning
confidence: 99%
“…Sessions were also audio-recorded with participant consent. We explored the nurse interventionist notes using content analysis (Denis, 2014; Price et al, 2014), which focused on the experiences of a small number of participants rather than those of a larger group, with the goal of giving voice to those whose stories had not been heard in published literature. Specifically, we explored themes related to the sharing of sensitive personal information within families in China, a setting of low mental-health resources and high HIV-related stigma (Li et al, 2009).…”
Section: Methodsmentioning
confidence: 99%